Prasasti Batu Gong : Studi Historis Peninggalan Sejarah Lokal Jember yang Terbengkalai - Septian Andi Cahyo, M Agus Gunawan, Moch Lukman Hakim, Ilfiana Firzaq Arifin (LP4MK STKIP PGRI Lubuklinggau, 2025)
Local history is a branch of history that is interesting to discuss the culture or history of a region. One of Jember's local historical relics is the stone gong inscription. The Batu Gong Inscription is located in Kaliputh, Rambipuji District. This inscription is thought to have existed since the 7th – 8th century AD. This inscription was discovered by Dutch archaeologist W.F. Stutterheim and H.R. Heekeren in 1933. The aim of this research is to analyze the various factors that caused this inscription to receive less attention and outline the historical context of the Batu Gong inscription in the development of local Jember history which reflects the culture and traditions of the community at that time. This research uses literature, observation and interview methods. Factors in which the stone gong inscriptions have been neglected are lack of attention from the government and society, lack of promotion and education, as well as lack of coordination and governance. It can be seen from the literature that the role of government and society is very necessary. The government can be a motivator, facilitator and dynamist in preserving the Batu Gong Inscription.